2010
DOI: 10.1007/s10618-009-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

A clustering comparison measure using density profiles and its application to the discovery of alternate clusterings

Abstract: Data clustering is a fundamental and very popular method of data analysis. Its subjective nature, however, means that different clustering algorithms or different parameter settings can produce widely varying and sometimes conflicting results. This has led to the use of clustering comparison measures to quantify the degree of similarity between alternative clusterings. Existing measures, though, can be limited in their ability to assess similarity and sometimes generate unintuitive results. They also cannot be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 39 publications
(65 reference statements)
0
44
0
Order By: Relevance
“…In traditional clustering of points, it was found that clusterings could be similar in memberships, but their points are distributed very differently. This could lead to counter-intuitive situations where such clusterings were considered similar [5] [6]. We show the same scenario occurs when comparing graph clusterings.…”
Section: Introductionmentioning
confidence: 70%
“…In traditional clustering of points, it was found that clusterings could be similar in memberships, but their points are distributed very differently. This could lead to counter-intuitive situations where such clusterings were considered similar [5] [6]. We show the same scenario occurs when comparing graph clusterings.…”
Section: Introductionmentioning
confidence: 70%
“…Hierarchical cluster analysis is a type of technology with a multivariate numerical analytical method, by measuring the distances between the samples to confirm their similarities [38]. It uses the fact that the samples that are close to each other cluster more quickly than those that are far away from each other.…”
Section: The Methods Of Hierarchical Cluster Analysismentioning
confidence: 99%
“…Data mining has been applied with success in different fields of knowledge and in the last few years, it has been increasingly used in medical literature [10,11]. One of the objectives of data mining in clinical medicine is to create models that can use specific patient information to predict the outcome of interest and to support clinical decision-making or form the basis of hypotheses for future experiments.…”
Section: Predictive Data Mining In Abi Rehabilitationmentioning
confidence: 99%
“…If s,j, ieN are the MLP layer, node and input counters respectively, for each W(t) component, w j, s '(t) e R, an d being ijgR* the learning rate, then the weight reinforcement in each iteration is given by: (11) So, as the pdf weighting function proposed is the distribution of the input patterns that does not depend on the network parameters, the AMMLP algorithm can then be summarized as a weighting operation for updating each weight in each MLP learning iteration A*w = w*(x)Aw (12) being Aw = w(t + 1) -w{t) the weight updating value obtained by usual BPA and w*(x) the realization of the described weighting function w*(x) for each input training pattern x.…”
Section: Amp In Gradient Descent Algorithmmentioning
confidence: 99%